1990
DOI: 10.1111/j.1365-2125.1990.tb03793.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of dapsone to a cytotoxic metabolite: in vitro use of a novel two compartment system which contains human tissues.

Abstract: 1 A two compartment system, comprising two adjacent teflon chambers separated by a semi-permeable membrane, has been devised with which to investigate the generation of drug metabolites that are toxic to human cells in vitro. 2 Compartment A contained a drug-metabolising system (human liver microsomes ± NADPH) and compartment B contained target cells (human mononuclear leucocytes). The semi-permeable membrane retained protein (m.w. > 10,000) but allowed equilibration (within 1 h) of drug and drug metabolites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Microsomes was added to one compartment (compartment A) of a two compartment system in which two Teflon® chambers are separated by a semi-permeable membrane, as described previously (Riley et al, 1990;Tingle et al, 1990). Dapsone (100 ,UM) was added to compartment A in dimethyl sulphoxide (5 pu) followed by the addition of NADPH (1 mM).…”
Section: Methodsmentioning
confidence: 99%
“…Microsomes was added to one compartment (compartment A) of a two compartment system in which two Teflon® chambers are separated by a semi-permeable membrane, as described previously (Riley et al, 1990;Tingle et al, 1990). Dapsone (100 ,UM) was added to compartment A in dimethyl sulphoxide (5 pu) followed by the addition of NADPH (1 mM).…”
Section: Methodsmentioning
confidence: 99%
“…However, in these simple assays it is not possible to evaluate the effect of microsomal adherence to the target cell or to determine whether the toxic metabolite(s) formed can diffuse from the site of production and lead to tissue damage at some distance away. We have therefore employed a two compartment system (Riley et al, 1990) in which the activating system (human liver microsomes) is separated from the target cells (human erythrocytes, RBC) by a semipermeable membrane.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these simple assays it is not possible to evaluate the effect of microsomal adherence to the target cell or to determine whether the toxic metabolite(s) formed can diffuse from the site of production and lead to tissue damage at some distance away. We have therefore employed a two compartment system (Riley et al, 1990) in which the activating system (human liver microsomes) is separated from the target cells (human erythrocytes, RBC) by a semipermeable membrane.This method has been applied to the investigation of the toxicity of dapsone and some of its putative metabolites toward human red cells in the presence of microsomes prepared from human liver. In addition, we have also screened a series of drugs structurally related to dapsone as well as known inhibitors of cytochrome P-450 for their ability to inhibit the metabolism of dapsone in an attempt to decrease the adverse events associated with administration of this drug.…”
mentioning
confidence: 99%
“…In addition, basic structural requirements for the bioactivation of aromatic anticonvulsants and the aldose reductase inhibitor sorbinil were proposed [10]. Human hepatie microsomal P450 enzymes selectively metabolized mianserin, a tetracyclic antidepressant, to a cytotoxic form [8,10] and were much more efficient at bioactivating dapsone than even induced murine microsomes [11], suggesting a predominant role of constitutive human P450 enzymes in the bioactivation of both these compounds. Indeed, Fleming and colleagues have since confirmed that a major human P450 isoform CYP3A4, catalyses the conversion of dapsone to its pro-reactive hydroxylamine metabolite [12].…”
Section: More Recent Approachesmentioning
confidence: 99%
“…Several earlier investigations, ineluding the use of cells from individuals deficient in GSHsynthesizing enzymes (expressed clinically as 5-oxoprolinuria), have also indicated a pivotal role of GSH and/or GSHdependent enzymes in sulphonamide toxicity [4]. Sulphonamides (and dapsone) exert their toxic effects through hydroxylamine or nitroso metabolites, and their toxicity in this assay can be attenuated by the inclusion of exogenous GSH [4,11]. However, this tripeptide is unable to penetrate cells [15], and hence the cytoprotectlve effects observed in our studies [ 11 ] and that of Carr and co-workers [14] must be exerted extracellularly, either via conjunction of the reactive metabolites, or by preventing the oxidation of the hydroxylamines to more reactive species.…”
Section: Sulphonamide Hypersensitivity Reactions and Infectionmentioning
confidence: 99%